'Havelock Wilson Exposed' - Minority Movement pamphlet, 1926 (1926)
1926 1918-1939 "'Havelock Wilson Exposed' - Minority Movement pamphlet, 1926" [T0289.jpg], 1926, Seaman's Section of the Transport Workers' Minority Movement This pamphlet, published by the seaman's section of the Transport Workers' Minority Movement, attacks the leadership of the National Union of Seamen. It also demands improvements in seamen's conditions, including a 48 hours week, clean bedding and a free passage home for seamen left in port due to sickness.